2022
DOI: 10.4037/ajcc2022732
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Barthel Index Used at Intensive Care Unit Discharge

Abstract: Background The Barthel Index, originally developed and validated to assess activities of daily living in patients with neuromuscular disorders, is commonly used in research and clinical practice involving critically ill patients. Objectives To evaluate the internal consistency, reliability, measurement error, and construct validity of the Barthel Index used at intensive care unit discharge. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…How does the study by Stripari Schujmann et al (1) compare with others measuring the BI? In a cohort of 122 general ICU patients from the pre-COVID era, the median (interquartile range [IQR]) BI score at ICU discharge was 25 (10–60; rater 1) (3). In the seminal randomized clinical trial of early physical therapy and occupational therapy, the median (IQR) BI scores at hospital discharge for those who started rehabilitation within 72 hours of ICU admission was 75 (IQR 7.5–95), and those in the control group 55 (0–85) (4).…”
Section: Contextualizing the Resultsmentioning
confidence: 99%
“…How does the study by Stripari Schujmann et al (1) compare with others measuring the BI? In a cohort of 122 general ICU patients from the pre-COVID era, the median (interquartile range [IQR]) BI score at ICU discharge was 25 (10–60; rater 1) (3). In the seminal randomized clinical trial of early physical therapy and occupational therapy, the median (IQR) BI scores at hospital discharge for those who started rehabilitation within 72 hours of ICU admission was 75 (IQR 7.5–95), and those in the control group 55 (0–85) (4).…”
Section: Contextualizing the Resultsmentioning
confidence: 99%
“…In this sense, other studies have validated the Barthel Index for other populations. A study carried out with the Brazilian population investigated the measurement properties of the Barthel Index in intensive care unit discharge and observed adequate internal consistency (Cronbach's alpha = 0.81), acceptable reliability (ICC = 0.98), and moderate to high correlations with other physical functioning measurement instruments (rho = 0.57 to 0.88) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…It showed su cient inter-rater reliability (ICC 0.98) and good internal consistency (Cronbach's α 0.81) supported by a low certainty of evidence but was rated indeterminate for internal consistency due to no information on structural validity (52). Su cient construct validity was supported by a high certainty of evidence (52,54). Su cient responsiveness was demonstrated in a single study with a very low certainty of evidence (51).…”
Section: Activities Of Daily Livingmentioning
confidence: 96%
“…Four studies reported data for the Barthel Index (51)(52)(53)(54). It showed su cient inter-rater reliability (ICC 0.98) and good internal consistency (Cronbach's α 0.81) supported by a low certainty of evidence but was rated indeterminate for internal consistency due to no information on structural validity (52). Su cient construct validity was supported by a high certainty of evidence (52,54).…”
Section: Activities Of Daily Livingmentioning
confidence: 99%
See 1 more Smart Citation